Development of a Short Course on Urban and Peri-Urban Food Production in - Eleni Pliakoni; George Nonos (Urban Food Systems Symposium, 2022)
Urban and peri-urban food production is a tool to reduce poverty, malnutrition, unemployment, but also improve self-esteem and skill development among more positive outcomes. In Greece, many farms are peri-urban, and the involved farmers produce fruits and vegetables for local distribution. Also, many individuals practice fruit and vegetable production in an urban environment without any expertise. However, there is no specialization or field of studies or specialists in Urban Food Production. Therefore, a need was identified for the development of a short course on Urban and Peri-Urban Food Production that would provide applicable knowledge for managing in an environmentally friendly way urban vacant lots and peri-urban agricultural land to intensively produce vegetables, aromatic/medicinal plants, and fruits. In 2017 as part of the Greek Diaspora Fellowship Program, we developed and delivered a two-weekend long short course. Our main goal was to develop an undergraduate and continuing education curriculum for small-scale local food production. Our target audience were undergraduate students in Agriculture, agriculturists, professional farmers and farmworkers, unemployed citizens, and hobbyist gardeners. The topics covered were: Basic characteristics of Urban Food Production; Natural resource availability and use for urban food production; Community gardens; Open field vegetable growing in the peri-urban environment and the garden; Protected vegetable production for local consumption; Local small-scale fruit tree production; Plant protection in the urban and peri-urban environment; Harvest and handling locally produced fresh commodities. Each participant was required to develop a short project on Urban or Peri-Urban farming with different case studies including private gardens, schoolyards, and profit-oriented peri-urban cases among others. Participants evaluated the course very positively pointing out that knowledge on this subject was well delivered and very useful. The course was offered two weekends in March 2017 at the University of Thessaly, Greece and had more than 80 participants. Videos from all lectures were made available at the University’s web site. This paper will discuss how the short course was developed and delivered as well as students’ evaluations and future needs.
Keywords: continuous education; local food production; municipal vegetable gardens